Fundamentals of Computational Methods for Engineers - Rana, Masud; Xu, Wei (Electrical engineering teacher); Guo, Youguang (Bentham Science Publishers, 2022)
This textbook bridges the gap between introductory and advanced numerical methods for engineering students. The book initially introduces readers to numerical methods before progressing to linear and nonlinear equations. Next, the book covers the topics of interpolation, curve fitting and approximation, integration, differentiation and differential equations. The book concludes with a chapter on advanced mathematical analysis which explains methods for finite difference, method of moments and finite elements. The book introduces readers to key concepts in engineering such as error analysis, al.